2022
DOI: 10.1007/s12178-022-09788-x
|View full text |Cite
|
Sign up to set email alerts
|

Common Ultrasound Applications for Pediatric Musculoskeletal Conditions

Abstract: Purpose of Review To discuss the use of ultrasound for diagnosis and management of common pediatric musculoskeletal conditions through a case-based approach. Recent Findings Ultrasound is an essential diagnostic modality in the early detection of developmental dysplasia of the hips and can be used as early as 6 weeks of age when the ossific nucleus has not developed yet. Ultrasound is helpful in diagnosing traumatic injuries such as fractures and intramusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…19 Children are about ten times more radiosensitive compared with adults, which is the result of their smaller body size and higher mitotic activity. 20 In Germany alone, approximately 40 million extremity radiographs were performed in 2014. 21 A study revealed that 82.8% of the radiographs completed on children, for suspected fractures, provided no diagnostic evidence of a fracture.…”
mentioning
confidence: 99%
“…19 Children are about ten times more radiosensitive compared with adults, which is the result of their smaller body size and higher mitotic activity. 20 In Germany alone, approximately 40 million extremity radiographs were performed in 2014. 21 A study revealed that 82.8% of the radiographs completed on children, for suspected fractures, provided no diagnostic evidence of a fracture.…”
mentioning
confidence: 99%
“…At the knee region in a 3-year-old child, the non-ossified patella appeared anechoic, mimicking effusion or a ganglion cyst. Furthermore, the growth plates manifest as discontinuity over the end of long bones, which can be misrecognized as fractures [ 4 ]. All of the aforementioned factors might lead to difficulty in interpreting pediatric knee ultrasound examinations.…”
mentioning
confidence: 99%